2004
DOI: 10.1158/0008-5472.can-04-2323
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbon-DNA Adducts in Prostate Cancer

Abstract: The formation of DNA adducts can lead to DNA replication errors and the potential for carcinogenesis. DNA adducts have been detected in prostate cells, but the distribution of adducts with respect to prostate cancer risk factors and histology is unknown. In a study of 130 Caucasian (n ‫؍‬ 61) and African-American (n ‫؍‬ 69) men with prostate cancer who underwent radical prostatectomy, we quantified polycyclic aromatic hydrocarbon (PAH)-DNA adducts in prostate tumor and adjacent nontumor cells by immunohistoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 35 publications
6
41
3
Order By: Relevance
“…Contrary to our findings on ESCC, some studies on the role of PAHs in prostatic cancer do not strongly support the role of PAHs in prostatic cancer risk (Rybicki et al, 2004;John et al, 2009).…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our findings on ESCC, some studies on the role of PAHs in prostatic cancer do not strongly support the role of PAHs in prostatic cancer risk (Rybicki et al, 2004;John et al, 2009).…”
Section: Discussioncontrasting
confidence: 99%
“…Associations between prostate cancer and specific occupational PAH exposure sources have also been reported [14,15]. In addition, we have recently shown that PAH-DNA adducts form in the prostate, and vary in level according to cellular histology [16].…”
Section: Introductionmentioning
confidence: 70%
“…Even for three-way interactions, assuming the third factor was evenly distributed across cases, our sample afforded the ability to detect iOR for the third factor of 2.1 or greater with 80 percent statistical power. Our study lacked a measure of biologically effective dose, but we have demonstrated in a previous study of a subset of cases drawn from this same study population that PAH-DNA adducts are detectable in the prostate epithelial cells of cases [16].…”
Section: Discussionmentioning
confidence: 99%
“…The study design and population have been described elsewhere (13). Briefly, the study population was composed of men from a larger case (n = 637) and control (n = 244) study who were diagnosed with prostate cancer and underwent radical prostatectomy (n = 395; 62.0%) or transurethral resection (n = 5; 0.7%) for treatment within the Henry Ford Health System, a network of facilities comprising an 800-bed hospital in the City of Detroit, Michigan, three smaller hospitals in surrounding suburbs, and 31 medical clinics located throughout the Metropolitan Detroit area.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, many prior studies have relied upon self-reported measures from a single source; however, PAH-DNA adducts serve as a biological marker of the effective PAH dose from all sources, particularly when quantified in the target tissue. We previously observed that PAH-DNA adducts are present in human prostate cancer cells and vary with tumor characteristics (13).…”
Section: Introductionmentioning
confidence: 99%